1999
DOI: 10.1159/000028271
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Cocaine Treatment Changes Expression of Mouse Liver Cytochrome P450 Isoforms

Abstract: Acute administration of single high doses of cocaine (50 or 60 mg/kg) produces liver injury in mice that have been pretreated with inducers of mixed function oxidases. Multiple low doses of cocaine (10–30 mg/kg) will produce hepatotoxicity without prior induction. To establish whether cocaine can induce its own activation, mice were given three daily injections of cocaine. Total cytochrome P450 content of the liver did not change. After 3 days the amount of cytochrome P450 2B10, as measured by pentoxy resorufi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…The effect of chronic cocaine administration on its own pharmacokinetics and metabolite pro®le is not clear. In-vitro, microsomal studies suggest that cocaine pretreatment may enhance cocaine metabolite formation (Sandberg et al 1993;Powers & Shuster 1999). However, we did not observe a change in the pharmacokinetics of cocaine or its metabolite formation after prolonged cocaine infusion.…”
Section: Parametercontrasting
confidence: 64%
“…The effect of chronic cocaine administration on its own pharmacokinetics and metabolite pro®le is not clear. In-vitro, microsomal studies suggest that cocaine pretreatment may enhance cocaine metabolite formation (Sandberg et al 1993;Powers & Shuster 1999). However, we did not observe a change in the pharmacokinetics of cocaine or its metabolite formation after prolonged cocaine infusion.…”
Section: Parametercontrasting
confidence: 64%
“…They presented evidence that cocaine administered chronically damaged the liver, and discussed the possibility that cocaine itself induced mixed-function oxidase in the smooth endoplasmic reticulum. Later studies have demonstrated that subacute cocaine treatment accounts for increased Nhydroxilation of norcocaine in the mouse liver (21).…”
Section: Resultsmentioning
confidence: 99%
“…27 28 Since chronic application of drugs that are metabolized by cytochrome P450, e.g. cocaine, 29 theophylline and midazolam, 30 can induce metabolism of cytochrome P450, it is possible that a similar phenomenon could be responsible for the decrease in the total and free plasma concentration of ropivacaine during chronic administration. Any other incidents interfering with ropivacaine metabolism can be excluded in our study.…”
Section: Discussionmentioning
confidence: 99%